Selected issues of state regulation of housing and communal services - E. V. Zgonnikov; E. A. Astakhova (Вестник Северо-Кавказского федерального университета)
Introduction. Housing and communal services is a rather complex multisectoral system. To ensure its high-quality functioning, it is necessary to develop effective effective mechanisms of state regulation. In this regard, it is important to conduct a qualitative analysis of the state of the housing and communal services sector and identify ways to solve the identified problems.Goal. Study of certain aspects of the functioning of the housing and communal services sector and identify areas for improving its efficiency.Materials and methods. The study is based on a statistical analysis of indicators of the state of the housing and communal services sector using the method of comparison and formal logic. Results and discussion. As a result of the analysis, the directions for improving state regulation of the housing and communal services sector have been identified, and the need to tighten the licensing process and state control of business activities for managing apartment buildings has been substantiated. Conclusion. Based on the results of the study, it can be concluded that the proposed measures will increase the level of state regulation of the housing and communal services sector through the active introduction of digital technologies, as well as stricter licensing requirements for management companies.